2021
DOI: 10.3389/feart.2021.660579
|View full text |Cite|
|
Sign up to set email alerts
|

Debris Flow Assessment in the Gaizi-Bulunkou Section of Karakoram Highway

Abstract: Highways frequently run through the flow and accumulation areas of debris flow gullies and thus are susceptible to debris flow hazards. Assessing debris flows along highways can provide references for highway planners and debris flow control, emergency management. However, the existing assessment methods mostly neglect the essential information of the flow paths and spreading areas of debris flows at the regional scale. Taking the Gaizi Village-Bulunkou Township Section (hereinafter referred to as “the Gaizi-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Flow-R, a distributed empirical model, was implemented with great success not only in this study but also in many studies in the literature. Giano et al [2], Polat and Erik [60], Charbel and El Hage Hassan [50], and Jiang et al [51] discussed whether Flow-R and observed landslide runout results are compatible. The researchers concluded that Flow-R results are well matched with the observed results.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Flow-R, a distributed empirical model, was implemented with great success not only in this study but also in many studies in the literature. Giano et al [2], Polat and Erik [60], Charbel and El Hage Hassan [50], and Jiang et al [51] discussed whether Flow-R and observed landslide runout results are compatible. The researchers concluded that Flow-R results are well matched with the observed results.…”
Section: Discussionmentioning
confidence: 99%
“…Back-calculated debris flow velocities were observed in the range of 5 to 15 m/s in a study by Prochaska et al [106]. Similarly, different researchers considered different velocity values in the literature, e.g., 5 m/s [49], 10 m/s [37], 15 m/s [42,47,54], 16 m/s [107], 20 m/s [46], and 25 m/s [51]. By considering both back analyses and the local information obtained by residents having memorials related to the shallow landslides that occurred in May 1998 in this region, it was concluded that the velocity parameter could be set as 15 m/s for shallow landslides in the Eocene flysch facies.…”
Section: Selection Of Model Parametersmentioning
confidence: 96%
See 3 more Smart Citations